Application of Response Surface Methodology for Optimizing the Therapeutic Activity of ZnO Nanoparticles Biosynthesized from Aspergillus niger - Ali Es-haghi; Mohammad Ehsan Taghavizadeh Yazdi; Mohammad Sharifalhoseini; Mohsen Baghani; Ehsan Yousefi; Abbas Rahdar; Francesco Baino (Biomimetics, 2021)
In this study, the biosynthesis of zinc oxide nanoparticles using Aspergillus niger (A/ZnO-NPs) is described. These particles have been characterized by UV–Vis spectrum analysis, X-ray powder diffraction, field emission scanning electron microscopy, and transmission electron microscopy. To use this biosynthesized nanoparticle as an antiproliferative and antimicrobial agent, the IC50 value against the breast cancer cell line and inhibition zone against Escherichia coli were used to optimize the effect of two processing factors including dose of filtrate fungi cell and temperature. The biosynthesized A/ZnO-NPs had an absorbance band at 320 nm and spherical shapes. The mean particles size was 35 nm. RSM (response surface methodology) was utilized to investigate the outcome responses. The Model F-value of 12.21 and 7.29 implies that the model was significant for both responses. The contour plot against inhibition zone for temperature and dose showed that if the dose increases from 3.8 to 17.2 µg/mL, the inhibition zone increases up to 35 mm. As an alternative to chemical and/or physical methods, biosynthesizing zinc oxide NPs through fungi extracts can serve as a more facile and eco-friendly strategy. Additionally, for optimization of the processes, the outcome responses in the biomedical available test can be used in the synthesis of ZnO-NPs that are utilized for large-scale production in various medical applications.